An Analysis of Politeness Rules in Teacher-Students Classroom Interaction - Kamilah, Siti Nur (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
The practical application of manners or etiquette to avoid offending and to make others feel comfortable is known as politeness. Since it is a culturally determined phenomenon, what is considered to be respectful in one society may occasionally be viewed as extremely impolite or strange in another. This descriptive qualitative study seeks to investigate the rules of politeness by Lakoff (1973) in teacher-students utterances during classroom interaction. However, an English teacher and 36 students of MAN 2 Kota Kediri became the sample of this research. As the data was a speech-shaped, it was obtained through several steps such as observation and data recording then it was analyzed trough data reduction, and data display, data validation, and drawing conclusion. The findings indicated that there were three rules used by the teacher and the students in their utterances namely ‘Do Not Impose’, ‘Give Option’, and ‘Make the Hearer Feel Good’.